Bermain Peran (Role Playing) dalam Pembelajaran Maharah Al-Kalam di PKPBA UIN Maliki Malang - Sa’diyah, Halimatus (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2018)
The focus in this research study is how to play the role or role playing in learning speaking skills in the PKPBA of UIN Maliki Malang? Based on this focus, this study aims to describe role playing in learning speaking skills in PKPBA of UIN Maliki Malang. The type of this research is qualitative and uses two techniques in data collection, namely observation and documentation. For the data obtained in this study, it is descriptive which is then analyzed inductively. From this study found several results of the study, namely the existence of learning plans that are in accordance with the learning objectives of speaking skills in PKPBA of UIN Maliki Malang by using role playing, found the advantages and disadvantages of role playing in learning speaking skills and the existence of learning materials that can be used as texts in role playing.